Development of Patients with Ventilator Care Model to Prevent Ventilator Associated Pneumonia In Ranong Hospital - Nakrod, Sirirat; Oucharoen, Niramol; Nakarit, Kanlayanee (Journal of The Royal Thai Army Nurses, 2020)
The purpose of this research and development were to develop a model for take care of patient with ventilator to prevent ventilator associated pneumonia in Ranong Hospital. The sample group were 88 nursing personnel and the 301 patients of age more than 15 year old and were not affected by pneumonia on admission. Data were analyzed using descriptive and pair-sample t-test statistics. The results of the study found that more than 90% of participants felt that development of patient with ventilator care model to prevent ventilator associated pneumonia among nursing personnel. The knowledge score of nurses increased from 18.8 to 25.62. Correct practice rates in post-intervention phase 93.14% compared with 71.79% in pre-intervention. The mortality rate was reduced significantly (p <0.05). But VAP incidence rate, length of stay and duration of mechanical ventilation were not significantly different (p > 0.05). It could be concluded that that concept of collaborative quality improvement could be applied to develop a model for take care of patient with ventilator to prevent ventilator associated pneumonia among nursing personal in Ranong Hospital.